Poliovirus Protein 3A Inhibits Tumor Necrosis Factor (TNF)-Induced Apoptosis by Eliminating the TNF Receptor from the Cell Surface - Neznanov, Nickolay (American Society for Microbiology, 2001)
Viral infections often trigger host defensive reactions by activating intrinsic (intracellular) and extrinsic (receptor-mediated) apoptotic pathways. Poliovirus is known to encode an antiapoptotic function(s) suppressing the intrinsic pathway. Here, the effect of poliovirus nonstructural proteins on cell sensitivity to tumor necrosis factor (TNF)-induced (i.e., receptor-mediated) apoptosis was studied. This sensitivity is dramatically enhanced by the viral proteinase 2A, due, most likely, to inhibition of cellular translation. On the other hand, cells expressing poliovirus noncapsid proteins 3A and 2B exhibit strong TNF resistance. Expression of 3A neutralizes the proapoptotic activity of 2A and results in a specific suppression of TNF signaling, including the lack of activation of NF-κB, due to elimination of the TNF receptor from the cell surface. In agreement with this, poliovirus infection results in a dramatic decrease in TNF receptor abundance on the surfaces of infected cells as early as 4 h postinfection. Poliovirus proteins that confer resistance to TNF interfere with endoplasmic reticulum-Golgi protein trafficking, and their effect on TNF signaling can be imitated by brefeldin A, suggesting that the mechanism of poliovirus-mediated resistance to TNF is a result of aberrant TNF receptor trafficking.